INTERNAL MARKETING AND ORGANIZATIONAL CITIZENSHIP BEHAVIOUR (OCB) AMONG STAFF OF NIGERIAN ARMY UNIVERSITY BIU – BORNO STATE (UNIZIK Journal of Marketing, 2025)
This study investigated the influence of internal marketing practices - Employee Motivation (EM), Digital Internal Communication (DIC), Leadership Emotional Intelligence (LEI), and Diversity, Equity, and Inclusion (DEI) on Organizational Citizenship Behaviour (OCB) among academic staff at Nigerian Army University Biu (NAUB). Drawing on Social Exchange Theory (SET), the study contends that employees’ perceptions of organizational support through these internal mechanisms foster discretionary behaviours that strengthen institutional effectiveness. A cross-sectional survey design was employed, targeting the entire population of 356 academic staff. A census sampling technique was adopted, resulting in a sample size equal to the population. Data were collected using a structured questionnaire with items measured on a fivepoint Likert scale. The instrument was adapted from validated scales in existing literature, ensuring content and construct validity, while a pilot test confirmed reliability with Cronbach’s alpha values above 0.70 for all constructs. Data were analyzed using multiple regression analysis. Findings revealed that all four internal marketing practices significantly and positively predicted OCB, with LEI exerting the strongest influence, followed by EM, DEI, and DIC. The results underscore the importance of emotionally intelligent leadership and inclusive organizational practices in promoting citizenship-driven behaviours among academics. The study concludes that a supportive and inclusive internal environment is crucial for institutional resilience and academic excellence. It recommends structured recognition frameworks, robust digital communication systems, leadership development programmes emphasizing emotional intelligence, and comprehensive DEI strategies to enhance staff engagement and organizational performance.
Keywords: Internal Marketing, Organizational Citizenship Behaviour, Emotional Intelligence, Diversity and Inclusion, Higher Education, Social Exchange Theo